Analysis of damages on induction motors by the finite element method - Mazur, Damian (Computer Assisted Methods in Engineering and Science, 2023)
The results of computations of forces and moments in induction motor made with OPERA 2D program and possibilities of application of FEA methods to consider the failure states during the calculations of induction machine dynamics are discussed in this paper. A mathematics model of an induction motor makes it possible to perform the calculations and analysis of stator currents and electromagnetic torque when the rotor rotates eccentrically, as well as when a bar or rotor ring is broken. A tool has been created which enables to predict preliminarily the results of the defects, which might be introduced at the motor manufacturing stage. To calculate 3D free vibration frequencies of the rotor system of the motor under consideration the PATRAN package has been used. It allowed us to examine the resonance frequencies of the rotor. For the diagnostic measurements the MotorMonitor™ program has been applied. It was possible to attain high computational effectiveness due to parallel programming on CONVEX computers of ACC "CYFRONET".